Morbidity pattern and hospital outcome of neonates admitted in secondary care level hospital in Bangladesh - Ali, Md Ayub; Latif, T; Taher, MA (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):136-41. The abstract of this article is available on the PubMed website